A high-performance electroactive PPy/rGO/NiCo-LDH hybrid film for removal of dilute dodecyl sulfonate ions. (20th January 2020) - Wang, Jian; Gao, Fengfeng; Du, Xiao; Ma, Xuli; Hao, Xiaogang; Ma, Wenbiao; Wang, Kezhi; Guan, Guoqing; Abudula, Abuliti
Abstract: An electroactive ion exchange hybrid film of polypyrrole/reduced graphene oxide/NiCo-layered double hydroxide (PPy/rGO/NiCo-LDH) with three-dimensional (3D) "sand rose" flower-like structure was fabricated by a two-step electrodeposition method. NiCo-LDH nanosheets were electrodeposited on the surface of polypyrrole/graphene oxide (PPy/GO) conducting substrate for the removal of dodecyl sulfonate ions (DS − ions) with low concentrations. Herein, the electroreduction of GO to rGO enhanced the electron conductivity and the unique structure of hybrid PPy/rGO/NiCo-LDH film ensured the fast diffusion of electrons as well as ions. The electrochemical performance of hybrid film was characterized by cyclic voltammetry (CV) and electrochemical impedance spectrum (EIS), and the effects of the applied electrode potential, initial concentration of DS − ions and pH of the simulated wastewater on the uptake kinetics of DS − ions were investigated. As a result, the coexisting anions had no obvious effect on the adsorption of DS − ions and the removal percentage of DS − ions reached 92.31% in a 10 mg L −1 DS − solution with 0.8 V electrode potential. Especially, in the pH ranging from 5.0 to 9.0, the DS − ions were efficiently removed. In addition, the double-driven ion exchange mechanism coupling electric double-layer (EDL) effect of rGO and pseudo capacitance effect of PPy to remove DS − ions was proposed based on the X-ray photoelectron spectroscopy (XPS) and CV analyses. It is expected that such a novel PPy/rGO/NiCo-LDH hybrid electroactive ion-exchange film separation technology based on the double-driven mechanism could be a potential technique for wastewater treatment. Graphical abstract: Image 1 Highlights: A double-driven electroactive ion exchange hybrid film was fabricated. The charge capacity of the film retained 88.8% after 1000 successive cycles. The coexisting anions had a slight impact on the uptake of DS − ions. The removal of dilute DS − ions was achieved using the film in ESIX process.